Trakai Castle Court Acts of 1660–1661 in the Context of the Legal Communication of the Grand Duchy of Lithuania - Ушинскиене, Виктория (Slavistica Vilnensis, 2018)
[full article, abstract in Russian; abstract in Lithuanian and English] The paper deals with the previously unexplored Trakai Castle Court Acts of 1660–1661 (F7-MDGs, 1660–1661) from the collection of Vilnius University. The manuscript written in Polish and Ruthenian languages is important for research of Lithuanian, Polish, Russian and Byelorussian history. Information accumulated in it witnesses court activities, reflecting a broad political, social and cultural panorama of the multilingual GDL society. The abundance of accumulated information enables us to consider it as unique reference book that reflects changing sociolinguistic situation of the GDL. Chronologically ample documentary material is interesting and vital to the history of language, historical geography, and genealogy investigation. The article was prepared in the framework of the research project “Court books of the Grand Duchy of Lithuania (GDL): digitization and database” realized by Vilnius University Library (VUL, Nr. LIT-5-19).